Preparasi Karbon Aktif dari Sabut Kelapa dengan Aktivator Gelombang Mikro untuk Adsorpsi Rhodamin B - Nahdatul Aulia; Miftahul Khair (Jurnal Periodic Jurusan Kimia UNP, 2022)
Activated carbon from coconut husk has been prepared by using microwave assisted activation. Carbonization was conducted at mild condition of 250ºC for 105 minutes heating time. Optimum activated carbon is obtained by using microwave assisted activation at 300 watts of iradiation for 4 minutes contact time with iodine number is 779,7604 mg/g. Characterization of activated carbon using FTIR and proximate analysis (water content, vaporcontent, ash content, bound carbon content and iod absorption). Adsorption test showed that the prepared activated carbon was able to absorp Rhodamin B at the optimum concentration of 200 mg/L. Adsorption isoterm study conducted by Langmuir equation with a regression coefficient R2 = 0,9640 with a maximum absorption capacity of 2,923 mg/g. FTIR characterization showed that the activated carbon contains a fungsional groups O-H at wave numbers 3600-3200 cm-1, C=C at wave numbers 1500-1650 cm-1, and C-O at wave numbers 1300-900 cm-1.